Spectrum of clinical characteristics of chronic suppurative otitis media unsafe type: a retrospective study from a tertiary care teaching hospital in Central India - Hansdah, Rashmi; Sachdeva, Kavita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Chronic suppurative otitis media (CSOM)-unsafe type or atticoantral disease or chronic otitis media-squamosal type is a commonly encountered bone eroding disease of the middle ear whose complications can be potentially fatal. Methods: Retrospective analysis of 80 patients who underwent mastoid exploration in the department of otolaryngology and head and neck surgery, NSCBMCH, Jabalpur between June 2016 and May 2017. Results: Unsafe CSOM is commoner in young males of 16-30-year age group. Foul smelling, scanty, purulent ear discharge was the commonest symptom (97.5%). Attic perforation was the most consistent otoscopic finding (47.5% cases). 15% of our patients had central perforations. Conductive hearing loss was most common (62%) followed by mixed hearing loss (23%) and sensorineural hearing loss (11%). Commonest complication encountered was mastoiditis (27 cases). Mastoidectomy with tympanoplasty was done in almost all cases (97.5%). Attic (96.2%), additus (90%), and antrum (86.2%) were commonly involved by disease process. Incus was found to be most susceptible to erosion (88.5%) while stapes was most resistant (36.25%). Conclusions: Unsafe CSOM presenting late warrant prompt diagnosis and surgical intervention. Unusual presentation like retropharyngeal abscess and trismus should raise suspicion of complicated unsafe CSOM in patients with history of otorrhoea. Canal wall down mastoidectomy with rehabilitation of hearing is the surgery of choice in patients who are unlikely to follow up regularly.